Effects of dietary change on future consumer demand for major cereals: A range of scenarios - CGIAR Research Program on Wheat (2021)
This was part of a joint research project involving PIM, CRP Maize and CRP Rice. A number of case studies have been published as well as a synthesis report that can be used as basis for further research, band uptake by policy makers and foresight analysis.